EVALUASI AKURASI DAN PRESISI RESONATOR HELHOLTZ PADA LABORATORIUM FISIKA UIN SUNAN KALIJAGA - Frida Agung Rakhmadi; Dyah Imas Cholidina; Ayu Sakila Arum; Defanny Defanny; Cindy Septiani S; Ade Kurniawan; Agung Nugroho (UIN Sunan Kalijaga Yogyakarta, 2020)
Research on the accuracy and precision of the Helmholtz resonator evaluation at UIN Sunan Kalijaga physics laboratory has been conducted. This research is motivated by the absence of evaluation research on this tool since its arrival in 2008. This research was conducted in 3 stages, namely the preparation of tools and materials, data collection, and data processing. The results of this study provide information that the accuracy of the Helmholtz resonator in the UIN Sunan Kalijaga physics laboratory has decreased. The accuracy is still in the good category, even though it is under SNI and SI. While the precision is still very good and still meets SNI and SI.